2020
DOI: 10.1136/flgastro-2020-101563
|View full text |Cite
|
Sign up to set email alerts
|

Disease monitoring of biologic treatment in IBD: early impact and future implications of COVID-19 pandemic

Abstract: COVID-19 has dominated life in 2020 with, at the time of writing, over 4.9M global cases and >320 000 deaths. The impact has been most intensely felt in acute and critical care environments. However, with most UK elective work postponed, laboratory testing of faecal calprotectin halted due to potential risk of viral transmission and non-emergency endoscopies and surgeries cancelled, the secondary impact on chronic illnesses such as inflammatory bowel disease (IBD) is becoming apparent. Data from the Scottis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Worsening in IBD symptoms could be caused by the reduction in therapeutic drug monitoring, widespread cancelation of elective procedures (i.e., endoscopies), and outpatient activity (i.e., infusion centers, clinic appointments). 22 Our study also reported worsening asthma and COPD symptoms, which was supported by the GINA and CAT scores during the pandemic compared to the prepandemic. The impact on asthma and COPD may have been caused by limited access to several diagnosis procedures and reduction in usual medical care.…”
Section: Discussionsupporting
confidence: 76%
“…Worsening in IBD symptoms could be caused by the reduction in therapeutic drug monitoring, widespread cancelation of elective procedures (i.e., endoscopies), and outpatient activity (i.e., infusion centers, clinic appointments). 22 Our study also reported worsening asthma and COPD symptoms, which was supported by the GINA and CAT scores during the pandemic compared to the prepandemic. The impact on asthma and COPD may have been caused by limited access to several diagnosis procedures and reduction in usual medical care.…”
Section: Discussionsupporting
confidence: 76%
“…Thus the use of TDM was reduced 26 . This observation has been made elsewhere and if prolonged may have consequences, with the potential for inappropriate dosing, drug toxicity or loss of response 27 . The development of point of care assays 28 and methods for remote TDM (for example, using dried blood spots) 29 may allow us to overcome these new barriers to TDM.…”
Section: Discussionmentioning
confidence: 99%
“…POC tests may be suitable for patients living in a remote geographical area or those who wish to minimise contact with healthcare facilities. 36 …”
Section: Faecal Calprotectinmentioning
confidence: 99%